2020
DOI: 10.1097/j.pain.0000000000001860
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mindfulness-based stress reduction in episodic migraine: a randomized clinical trial with magnetic resonance imaging outcomes

Abstract: Longitudinal Data in Two Groups Longitudinal Data in Two Groups with interaction of covariate by group 42 Adapting the CAT12 workflow for unusual populations Customized Tissue Probability Maps 46 Customized DARTEL-template Other variants of computational morphometry Deformation-based morphometry (DBM) Surface-based morphometry (SBM) Region of interest (ROI) analysis Additional information on native, normalized and modulated volumes Naming convention of output files Calling CAT from the UNIX command line Techni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 97 publications
9
114
0
Order By: Relevance
“…Consequently, a more skilful approach and a new perspective could be utilizing (Ghawadra et al., 2019; Gu et al., 2020), thereby reducing emotional exhaustion and depersonalization. Meanwhile, studies showed that long‐term mindfulness meditation training could thicken the cerebral cortex responsible for attention and comprehensive emotions, shrink the amygdala related to fear emotions and strengthen the function of the insula (Seminowicz et al., 2020; Yuan et al., 2020), which lead the individuals to be more positive and optimistic. These studies proved that the effect of mindfulness on emotional exhaustion from the perspective of neurophysiological mechanism, and depersonalization is the result of emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a more skilful approach and a new perspective could be utilizing (Ghawadra et al., 2019; Gu et al., 2020), thereby reducing emotional exhaustion and depersonalization. Meanwhile, studies showed that long‐term mindfulness meditation training could thicken the cerebral cortex responsible for attention and comprehensive emotions, shrink the amygdala related to fear emotions and strengthen the function of the insula (Seminowicz et al., 2020; Yuan et al., 2020), which lead the individuals to be more positive and optimistic. These studies proved that the effect of mindfulness on emotional exhaustion from the perspective of neurophysiological mechanism, and depersonalization is the result of emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…This secondary analysis utilized data from the MRI Outcomes of Mindfulness Meditation for Migraine clinical trial (NCT02133209). 17 Participants were enrolled from June 2014 to February 2017. The primary objective of the clinical trial was to determine the short and long term efficacy of MBSR+ on headache frequency, brain structure and function.…”
Section: Methodsmentioning
confidence: 99%
“…Patients may also have better sleep quality, related to MBSR and or improvement in headaches. This secondary data analysis from our clinical trial 17 assessed enhanced MRSR (MBSR+) as a comprehensive therapy for migraine. We hypothesized that a) compared to SMH, patients randomized to MBSR+ have greater improvement in sleep quality, anxiety, depression and stress symptoms over time compared to an active control treatment arm, b) baseline sleep quality, anxiety, depression and stress symptoms predict treatment response to MBSR+ and c) sleep quality, anxiety, depression and stress symptoms are mediators of the effect of MBSR+ on treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were recruited as part of two larger studies acquiring clinical, behavioral, and MRI data to examine biomarkers of chronic daily headache (patients with CM, Stanford University) and mindfulness based stress reduction for migraine (patients with EM, University of Maryland, Baltimore and Johns Hopkins University) 27 . Prior publications including these data 27,28 did not investigate amygdala structure and/or function between EM and CM in relation to headache and cognitive-affective measures. Patients were eligible for the current study if they were at least 18 years of age and met the diagnostic criteria for EM or CM with or without aura for at least three months according to the International Classification of Headache Disorders (ICHD)-3 1 , as determined by a physician.…”
Section: Methodsmentioning
confidence: 99%